Diffuse large B-cell lymphoma of the gallbladder arised 8 years after malignant lymphoma of the right testis: A case report and literature review. (2020) - Kai, Kengo; Hamada, Takeomi; Hiyoshi, Masahide; Imamura, Naoya; Yano, Koichi; Nagano, Motoaki; Kai, Masahiro; Hidaka, Tomonori; Shimoda, Kazuya; Haruyama, Yukihiro; Kataoka, Hiroaki; Nanashima, Atsushi
Highlights: Gallbladder involvement by lymphoma is extremely rare, and only 68 cases have been reported in the English literature so far. We experienced a case of diffuse large B-cell lymphoma (DLBCL) of the gallbladder arising 8 years after DLBCL of the right testis. We compiled and analysed reported cases in terms of background, symptoms, imaging findings, and prognosis. DLBCL was significantly more involved in other organs simultaneously or heterochronously in contrast of MALT lymphoma ( p = 0.004). Gallbladder lymphoma should be added to the differential diagnosis of gallbladder tumours. Abstract: Introduction: Gallbladder involvement in lymphoma is extremely rare, and only 68 cases have been reported in the English literature so far. We experienced a case of diffuse large B-cell lymphoma (DLBCL) of the gallbladder arising 8 years after DLBCL of the right testis. Presentation of case: A 68-year-old man underwent orchiectomy for malignant lymphoma of the right testis pathologically diagnosed as DLBCL 8 years ago. Systemic surveillance incidentally revealed a gallbladder tumour, and elective resection of the gallbladder bed of the liver was performed under a preoperative diagnosis of gallbladder cancer. The histopathological examination revealed DLBCL. At re-evaluation 3 months after surgery, he was diagnosed as having DLBCL involving the stomach. There had been no recurrence for 39 months after chemotherapy and radiation, but he suffered from a poor general condition due to protein-losing enteropathy and died of infection. Discussion: We compiled and analysed reported cases of malignant lymphomas involving the gallbladder in terms of background, symptoms, imaging findings, and prognosis. Compared to MALT lymphoma, DLBCL was significantly more involved in other organs simultaneously or heterochronously ( p = 0.004). Conclusion: Gallbladder lymphoma should be added to the differential diagnosis of gallbladder tumours, especially when clinical findings are not consistent with the typical course of gallbladder carcinoma and cholecystitis.